(untitled) (Journal of the College of Basic Education, 2022)
Downs’ syndrome is a genetic disease resulting from trisomy 21 chromosome. It was the first chromosomal abnormality discovered in humans and has also been observed in other primate.Patient and methods:The elbow crease associated with enamel anomalies in teeth was studied in 44 males and 16 Females patients with Down syndrome in mentally retarded institutions aged from 8-10 years in Baghdad city.Aim of study: The aim of the present study is to know the frequency of the presence or absence forms of this crease: in addition to know the relation between elbow crease and enamel anomalies in primaryand permanent teeth from the genetic side.